Comparative Methylome Analysis Reveals Perturbation of Host Epigenome in Chestnut Blight Fungus by a Hypovirus - Li, Ru; Zhou, Sisi; Li, Yongbing; Shen, Xiaorui; Wang, Zhiqiang; Chen, Baoshan (Frontiers in Microbiology, 2018)
In eukaryotic genomes, DNA methylation is an important type of epigenetic modification that plays crucial roles in many biological processes. To investigate the impact of a hypovirus infection on the methylome of Cryphonectria parasitica, the chestnut blight fungus, whole-genome bisulfite sequencing (WGBS) was employed to generate single-base resolution methylomes of the fungus with/without hypovirus infection. The results showed that hypovirus infection alters methylation in all three contexts (CG, CHG, and CHH), especially in gene promoters. A total of 600 differentially methylated regions (DMRs) were identified, of which 144 could be annotated to functional genes. RNA-seq analysis revealed that DNA methylation in promoter is negatively correlated with gene expression. Among DMRs, four genes were shown to be involved in conidiation, orange pigment production, and virulence. Taken together, our DNA methylomes analysis provide valuable insights into the understanding of the relationship between DNA methylation and hypovirus infection, as well as phenotypic traits in C. parasitica.